RISALAH NUR DAN GERAKAN TAREKAT DI TURKI: PERAN SAID NURSI PADA AWAL PEMERINTAHAN REPUBLIK - Muhammad Faiz (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2017)
This paper tries to describe the role of Risalah Nur movement and its relationship with the tariqa movement in Turkey, especially after the collapse of the Ottoman Caliphate and the early modern state of Turkey. The methodological study of this paper will refer to literature perspective, specifically historical analysis of the life of Said Nursi and his work Risalah Nur through the Nursi’s books and the other related literatures. My study is assuming that Risalah Nur plays an important role when the tariqa, mysticism/tasawuf teachings banned by the Turkish government since 1925. For some Muslim scholars the Risalah Nur written in Arabic and Turkish is considered as the treasures of Islamic knowledge in Turkey. In fact, the Risalah Nur is supposed to be a role model of the Islamic teachings in Muslim world in which the manuscript represents the essential contents of the Quran. The Risalah Nur is strongly referred to Sufism, which deals with the universal value of peace and love that must be relevant for Muslims and all human beings from time to time.